Strategi Komunikasi Dakwah Ustazah Oki Setiana Dewi di Media Sosial dalam Membangun Keterhubungan dengan Audiens melalui YouTube - Nisa, Pia Khoirotun; Zakaria, Zakaria; Istiqomah, Alfina Nur (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2024)
The digital era has presented social media as a new space for delivering da'wah messages. Ustazah Oki Setiana Dewi is one of the da'wah figures who utilizes Instagram and YouTube as the main platforms to build relationships with audiences. This research aims to answer two problem formulations: (1) How is Ustazah Oki Setiana Dewi's da'wah communication strategy on social media, especially Instagram and YouTube, in building a connection with the audience? (2) What are the forms of da'wah communication strategies applied by Ustazah Oki Setiana Dewi on the two platforms? This research uses a descriptive qualitative approach with a case study method. The paradigm used is interpretivism, which focuses on a deep understanding of the meaning behind the da'wah message and the audience's response to it. The theoretical foundation used is Al-Bayayuni's da'wah communication theory, which includes three main dimensions: informative, persuasive, and expressive. The data findings show that Ustazah Oki's da'wah communication strategy on Instagram and YouTube has significant differences. On YouTube, the da'wah content is educative and in-depth, utilizing a longer duration to discuss religious topics in a structured manner. This approach fulfills the informative dimension of Al-Bayayuni's theory. Meanwhile, on Instagram, Ustazah Oki uses a more concise, emotional, and interactive approach through reels, stories, and live features, which emphasize the persuasive and expressive dimensions. In-depth discussion reveals that Ustazah Oki's strategies on both platforms reflect adaptations to the characteristics of social media and their audiences. On YouTube, the audience is more focused on in-depth religious learning, while on Instagram, they are more interested in concise and inspirational dakwah content. This shows the importance of flexibility in da'wah communication strategies to reach diverse audiences in the digital era.